HUDUDIY IQTISODIY-IJTIMOIY TARAQQIYOTNI TAʼMINLASHDA KICHIK BIZNES VA TADBIRKORLIKNI RIVOJLANTIRISHNING SAMARALI MEXANIZMLARI (Marketing Journal, 2026)
AbstractThis article scientifically investigates the issues of developing small business andentrepreneurship in the socio-economic development of regions of Uzbekistan. Thepurpose of the research is to analyze the current state of small business andentrepreneurship development in the regions, identify problems, and developscientifically based solutions. Statistical analysis, correlation analysis, SWOT analysis,comparative analysis, and expert survey methods were used. The results show thatdespite the rapid development of small business and entrepreneurship in Uzbekistan,there are a number of challenges in financing, infrastructure, human resources training,and digitalization. The article proposes an improved model for developing smallbusiness and entrepreneurship, an innovative cluster approach, and a digitaltransformation strategy.Keywords: small business, entrepreneurship, regional development, socioeconomic development, innovation, cluster approach, digital transformation,financing, business environment, Uzbekistan.